Komunikasi Kriminal : AnalisisResepsi Untuk Melihat Pemaknaan Bagi Kepentingan Pembelaan - Achmad, Ardan (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2008)
The audience has been central in mass communication research from the very beginning. Initially the audience was perceived as an undifferentiated mass, as a passive target for persuasion and information, or as market of consumers of media products. Students of media effects soon came to recognize that actual audiences are made up of real social groups and are characterized by networks of interpersonal relationship through which effects are mediated Audiences can also resist influence in part because they have their own varied reasons for choosing to attend to the media message, or seeing it from criminal communication field, for the sake of defences interest in a court room, an individual, or group of individuals, or to be specifically, a defendant, can give different meanings to a preferred meeninq constructed by media, in line with his or their own interest, particularly in the form of an tdeological resistance interpretation.